P-092 LAPAROSCOPIC TRANS-PERITONEAL HERNIOPLASTY (TAPP) IN EMERGENCY. (13th October 2022) - Garbarino, S; Latham, L; Gianazza, S; Colombo, E M; Odeh, M; Palamara, N; Vigezzi, A; Costa, J; Inversini, D; Ietto, G; Carcano, G
Abstract:  : The aim efficacy and technical feasibility of TAPP operation by analyzing patients operated on incarcerated inguino-crural hernia in emergency setting. Materials and methods: In 1 year, we enrolled 8 urgent incarcerated hernia patients operated using laparoscopic trans-peritoneal approach (TAPP) operated on acutely for inguino-crural incarcerated hernia associated with suspected visceral ischemic damage. Results: We repaired 6 inguinal incarcerated hernia and 2 cases of crural hernia. Among 6 inguinal hernia, only one was recurrent. In one case the laparoscopic approach permitted to exclude an obstructed Spigelian hernia diagnosed through tomography. In another case, TAPP allowed to diagnose omental incarcerated Spigelian hernia. In 3 cases this approach permitted to diagnose concomitant unknown wall defects. All cases presented signs of small bowel obstruction. The content of the sac in three cases was small bowel, in other three cases it was omentum, and in other two cases it contained lipoma. None of the cases were converted to open technique. The operative average time was 95 min; the average hospital stay was 1.5 days. No chronic pain or recurrences were observed after a mean follow up time of 8 months. Conclusions: The repair of complicated inguino-crural with TAPP in emergency is not a standard treatment. In our experience the laparoscopic approach allowed a safe reduction of hernia, the observation of the feature of hernia content, the diagnosis and repair of unknown wall defect, and a crural defects and contralateral inguinal hernia.